Modeling the musculoskeletal loading in bone remodeling at the hip of a child. (October 2021) - Terryn, Pieter-Jan; Fernandes, Paulo R.; João, Filipa; Veloso, António; Baptista, Fátima
Highlights: The paper addresses the relevance of physical activity in bone health. It presents a computational model specific for a 7 years-old boy considering the musculoskeletal loading of typical activities of children of this age. The results show that weight bearing PA is more effective in bone remodeling when the musculoskeletal loading is more intense and of short duration. Abstract: Background and objectives: The mechanical load associated with physical activity affects the bone adaptation process. The bone adaptationeffect varies with age, being more effective during childhood and adolescence, particularly during pre-pubertal years. Bone-strengthening physical activity is recommended for children and adolescents. The number of time periods (bouts) per day of vigorous physical activity seems to be more important than the total cumulative time for optimal bone strength. So, the aim of this study was to evaluate the effects of weight-bearing physical activity on bone mineral density (BMD) of the proximal femur through computational simulation considering the intensity, exposure time (bouts) and regionalization of the results. Methods: For this purpose, a finite element model of a 7 year-old child femur was developed based on computed tomography images. Musculoskeletal loads were obtained from experimental kinematic data of weight-bearing physical activity performed by children of the same age (standing, walking, running, jumping). The effects of physical activity on BMD of several regions of interest of the femur were analyzed using a bone remodeling model. A daily accumulation of 400 min of physical activity (200 min walking and 200 min standing) was considered as reference, against with which the effects of additional 10 min loading bouts were compared: 10 min bouts of vigorous intensity physical activity vs. 10 min bouts of light to moderate intensity physical activity. Results: The simulations revealed greater increases in BMD associated with higher intensity and longer duration of physical activity. The largest BMD increases occurs during the first 10 min bout compared to longer durations and in less mineralized central regions compared to regions far from the neutral axis of the bone. Conclusion: Weight bearing physical activity is more effective in bone remodeling when the musculoskeletal loading is more intense and of short duration and, under these conditions, less mineralized regions are more positively impacted.